Unemployment Clubs in Russian Regions. Issue 6 (3rd May 2018) - Danilenko, Tatiana; Demidova, Olga; Signorelli, Marcello
ABSTRACT: In this article, we empirically investigate regional unemployment in Russia. We first detect the existence of two unemployment clubs, that is, regions with high (low) unemployment surrounded by regions with high (low) unemployment, and a group that comprises the remaining regions. We then apply a specially designed class of spatial-econometric models to regional data 2005–2012, using difference GMM, and we obtain partial confirmation of our two main hypotheses: (i) spatial effects for the high-high and low-low clubs regions differ significantly; and (ii) the determinants of unemployment of the two clubs significantly differ with respect to those of the remaining regions. Our results have key implications for the national- and regional-level policies.